Green Economy And Green Finance: A Bibliometric Analysis - Rozida Novtiani; Juliarto, Agung (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2025)
This study aims to examine the development of research trends on green economy and green finance in the 2015–2025 period using a bibliometric approach. Along with the increasing global attention to sustainability issues and environmental policies, this study provides a comprehensive understanding of the development of scientific literature in the field, including mapping publication trends, analyzing academic collaborations, and identifying the main themes that are the focus of research. This study uses a bibliometric analysis method based on Scopus data supported by R-Packages and Biblioshiny WebInterface software. The analysis process is carried out in five main stages, namely document searches based on relevant keywords, article selection according to predetermined criteria, data validation to ensure accuracy, research trend analysis, and data visualization using PRISMA flow diagrams to ensure transparency and systematicity in the selection of literature used. The results of the study indicate a significant increase in the number of publications related to the green economy and green finance, especially after 2020. The main trends in this study indicate a close relationship between the green economy and aspects of sustainable development, technological innovation, environmental policy, and sustainability-oriented investment. In addition, the level of international collaboration in this study is also quite high, with 30.63% of publications involving more than one country.